Antimicrobial therapy in severe infections - Bisso Andrade, Aland (2011)
Sepsis is considered a public health problem because severe infections still are a major cause of death worldwide. Within the comprehensive management of the patient with severe sepsis or septic shock, the early administration of an appropriate antimicrobial regimen is one of the key strategies for survival and for reducing morbidity and mortality. In this review, we describe the antimicrobial therapy for the following conditions: severe pneumonia, urosepsis, intra-abdominal infections, serious skin and soft tissue infections, bacterial meningitis, fungal sepsis, venous catheter-related infections, and sepsis of undetermined origin. It is necessary for physicians who take care of patients with serious infections, that they must know not only the clinical manifestations of each process, but also their epidemiological characteristics, local bacterial prevalence, resistance patterns and pharmacology of available antimicrobial agents in order to make the best decisions. Both guidelines and systematic reviews are fundamental tools for the management of serious infections.